Cross‐resistance to purified Bt proteins, Bt corn and Bt cotton in a Cry2Ab2‐corn resistant strain of Spodoptera frugiperda. Issue 12 (24th August 2017) - Yang, Fei; Kerns, David L; Head, Graham P; Price, Paula; Huang, Fangneng
Abstract: BACKGROUND: Gene‐pyramiding by combining two or more dissimilar Bacillus thuringiensis (Bt) proteins into a crop has been used to delay insect resistance. The durability of gene‐pyramiding can be reduced by cross‐resistance. Fall armyworm, Spodoptera frugiperda, is a major target pest of the Cry2Ab2 protein used in pyramided Bt corn and cotton. Here, we provide the first experimental evaluation of cross‐resistance in S. frugiperda selected with Cry2Ab2 corn to multiple Bt sources including purified Bt proteins, Bt corn and Bt cotton. RESULTS: Concentration − response bioassays showed that resistance ratios for Cry2Ab2‐resistant (RR) relative to Cry2Ab2‐susceptible (SS) S. frugiperda were −1.4 for Cry1F, 1.2 for Cry1A.105, >26.7 for Cry2Ab2, >10.0 for Cry2Ae and −1.1 for Vip3A. Larvae of Cry2Ab2‐heterozygous (RS), SS and RR S. frugiperda were all susceptible to Bt corn and Bt cotton containing Cry1 (Cry1F or Cry1A.105) and/or Vip3A proteins. Pyramided Bt cotton containing Cry1Ac + Cry2Ab2 or Cry1Ab + Cry2Ae were also effective against SS and RS, but not RR. CONCLUSION: These findings suggest that Cry2Ab2‐corn‐selected S. frugiperda is not cross‐resistant to Cry1F, Cry1A.105 or Vip3A protein, or corn and cotton plants containing these Bt proteins, but it can cause strong cross‐resistance to Cry2Ae and Bt crops expressing similar Bt proteins. © 2017 Society of Chemical Industry